Prediksi Jumlah Siswa Baru Pada SMK Negeri 2 Buton dengan Metode Regresi Linier dan Exponential Smoothing - Dodiman, Dodiman; Hidayah, Nurul; Asniati, Asniati (Program Studi Pendidikan Matematika, Fakultas Keguruan dan Ilmu Pendidikan, Universitas Dayanu Ikhsanuddin, 2024)
The role of education is very important in a nation because education is a top priority today. Education plays an important role in creating an intelligent and wise Indonesian state and nation. Education is carried out with the aim of improving the quality of people's lives and increasing the nation's competitiveness. To support the creation of quality education, adequate facilities and infrastructure are needed. SMK Negeri 2 Buton is an educational facility in Buton district, Southeast Sulawesi. SMK Negeri 2 Buton is experiencing problems in providing facilities such as the number of tables, chairs, etc., one of the main causes is the difficulty of knowing the number of students who will register in the coming year. Linear regression and exponential smoothing are methods that can be used to predict new students by utilizing past admissions data. So, the aim of this research is to predict the number of new students at SMK Negeri 2 Buton by utilizing linear regression and exponential smoothing. The data used in the research is new student data from 2011 to 2023. Application of new student predictions using linear regression and exponential smoothing methods at SMK Negeri 2 Buton shows a good prediction value, namely less than 21%. This means that the prediction method results are closer to the actual number of new student admissions. Prediction testing shows that the exponential smoothing method produces a smaller MAPE value than the linear regression method with a difference of 3.8%